Analisis Strategi Bisnis pada PT Ultrajaya Milk Industry dan Trading Company Tbk - Haqy Prasetya A (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the business strategy of PT Ultrajaya Milk Industry & Trading Company Tbk. Ultrajaya is a market leader in the Indonesian dairy industry, holding a 36% market share in UHT milk. This study examines external and internal factors influencing the company's strategic decisions. The results indicate that Ultrajaya needs to focus on market penetration and product development to maintain its competitive edge amid growing competition from both local and international brands. Additionally, the company must address financial challenges while leveraging its strong distribution network and strong brand awareness to retain its leadership position in the market. The analysis is further enriched by financial and operational insights from the company’s 2023 annual report, highlighting key aspects such as revenue growth, investment strategies, and risk management initiatives